Evaluation of Pediatric Chronic Urticaria with Emphasis on Clinical and Laboratory Characteristics and Treatment Response to Omalizumab: A Real-Life Experience from a Tertiary Allergy Center - Aylin Kont Özhan; Tuğba Arıkoğlu (MDPI AG, 2024)
Pediatric data on the clinical and etiologic features, treatment response, and use of omalizumab for chronic urticaria (CU) are quite limited. The aim of this study was to evaluate the clinical and demographic characteristics, laboratory findings, and response to treatment of CU in children. Children with a diagnosis of CU between 2019 and 2023 were included in the study. Information on demographic characteristics, clinical features, laboratory tests, provocation tests for inducible urticaria, urticaria activity scores (UAS7), and treatment responses were obtained from patients' medical records. A total of 150 children (50.7% male) with CU were enrolled in the study. A total of 14 (9.3%) patients had autoimmune diseases of which 11 (7.3%) had autoimmune thyroiditis. Overall, 97 (64.7%) patients had chronic spontaneous urticaria (CSU) and 53 (35.3%) had chronic inducible urticaria. A total of 16 patients who remained symptomatic despite high-dose antihistamines were treated with omalizumab, with a good response in 13 (81.3%) and a partial response in 3 (18.7%) patients. CSU accounts for the majority of pediatric CU, with the etiology being in part related to an autoimmune background. This study provides an overview of CU in children and demonstrates the safety and efficacy of treatment with omalizumab.